Hubungan Pengetahuan, Dukungan Keluarga dan Sikap Ibu Hamil terhadap Pemeriksaan Tes Triple Eliminasi di UPTD Puskesmas Pante Raya Kab.Bener Meriah Tahun 2022 - Era Adhaini; Nur Azizah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Perineal rupture is a common complication in vaginal delivery that can increase the risk of postpartum hemorrhage, infection, and maternal death. One of the factors that contribute to the occurrence of perineal rupture is the baby's birth weight. Babies with a birth weight ≥4000 grams can cause greater pressure on the mother's birth canal, increasing the possibility of perineal tissue tears. In Indonesia, 75% of mothers who give birth vaginally experience perineal lacerations, and postpartum hemorrhage is still the main cause of 40% of maternal deaths. Purpose: This study aims to determine the relationship between birth weight and the incidence of perineal rupture in normal deliveries at the Independent Midwife Practice of Lusi Marbun, Simalungun Regency in 2022. Method: This study used an observational analytical design with a case-control approach. A sample of 30 mothers giving birth was selected using the total sampling method. Data were analyzed using the Chi-square test to determine the relationship between birth weight and perineal rupture. Results: The study showed that the majority of infants had a birth weight <4000 grams (63.3%), and the majority of mothers experienced second-degree perineal rupture (70%). Bivariate analysis showed a significant relationship between birth weight and the incidence of perineal rupture (p-value = 0.000). Conclusion: There is a significant relationship between birth weight and the incidence of perineal rupture. The greater the infant's birth weight, the higher the risk of perineal rupture in the mother during labor. It is important for health workers to detect fetal weight early, provide nutritional education during pregnancy, and optimally prepare for labor to minimize the risk of complications.